2022
DOI: 10.1007/s00018-022-04497-7
|View full text |Cite
|
Sign up to set email alerts
|

Myocardin regulates exon usage in smooth muscle cells through induction of splicing regulatory factors

Abstract: Differentiation of smooth muscle cells (SMCs) depends on serum response factor (SRF) and its co-activator myocardin (MYOCD). The role of MYOCD for the SMC program of gene transcription is well established. In contrast, the role of MYOCD in control of SMC-specific alternative exon usage, including exon splicing, has not been explored. In the current work we identified four splicing factors (MBNL1, RBPMS, RBPMS2, and RBFOX2) that correlate with MYOCD across human SMC tissues. Forced expression of MYOCD family me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Other lines of evidence also suggest widespread functional cooperation of RBPMS and RBFOX proteins including: enrichment around RBPMS-regulated exons not only of RBPMS dual CAC binding motifs but also of RBFOX binding GCAUG motifs (Jacob et al, 2022); the identification of a GCAUG containing motif as the top intronic binding site for RBPMS in ES cells (Bartsch et al, 2021); and the association of both RBFOX and RBPMS binding motifs with ERG (E26 related gene protein)-repressed exons in HeLa cells (Saulnier et al, 2021). Furthermore, the SMC transcription factor MYOCD was recently found to indirectly drive a set of SMC AS changes via changes in the expression levels of RBPMS, RBFOX2 and MBNL1 (Liu et al, 2022), and both Rbpms and Mbnl1 were found by scRNA-Seq to be part of a contractile VSMC gene signature (Dobnikar et al, 2018). Indeed, it has been suggested that gastrointestinal dysfunction in myotonic dystrophy is associated with dysregulation of an MBNL1 regulated splicing program in visceral smooth muscle cells (Peterson & Cooper, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Other lines of evidence also suggest widespread functional cooperation of RBPMS and RBFOX proteins including: enrichment around RBPMS-regulated exons not only of RBPMS dual CAC binding motifs but also of RBFOX binding GCAUG motifs (Jacob et al, 2022); the identification of a GCAUG containing motif as the top intronic binding site for RBPMS in ES cells (Bartsch et al, 2021); and the association of both RBFOX and RBPMS binding motifs with ERG (E26 related gene protein)-repressed exons in HeLa cells (Saulnier et al, 2021). Furthermore, the SMC transcription factor MYOCD was recently found to indirectly drive a set of SMC AS changes via changes in the expression levels of RBPMS, RBFOX2 and MBNL1 (Liu et al, 2022), and both Rbpms and Mbnl1 were found by scRNA-Seq to be part of a contractile VSMC gene signature (Dobnikar et al, 2018). Indeed, it has been suggested that gastrointestinal dysfunction in myotonic dystrophy is associated with dysregulation of an MBNL1 regulated splicing program in visceral smooth muscle cells (Peterson & Cooper, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A critical link between RBPMS-regulated SM-AS and the mature VSMC transcriptional network is MYOCD. A recent study indicated that MYOCD transcriptionally upregulates RBPMS in VSMCs leading to SM-AS induction upon over-expression [65]. We have shown that RBPMS, in turn, activates splicing of the VSMC-specific exon 2a in MYOCD [7], which allows for the generation of an N-terminal truncated protein that has been shown, in vitro , to act as the optimal co-factor with SRF to drive expression of the CArG box genes when compared to the non-VSMC isoform (exon 2a skipped) [19].…”
Section: Discussionmentioning
confidence: 99%
“…6,7,26 Since myocardin is suggested to promote its own splicing, reduced myocardin expression may also affect the activity of the expressed myocardin. 22 Dysregulation of the Hippo pathway has been associated with various diseases, including vascular disease. 43,47 Understanding the molecular mechanisms and cellular processes involved in disease progression due to YAP/TAZ dysregulation can lead us to identify novel therapeutic targets.…”
Section: Yap/ Ta Z Tr Anscrip Tional Coac Ti Vato R Smentioning
confidence: 99%